Desarrollo de una aplicación web para el manejo del sistema de ventas y facturación en el Supermercado Don Cando, ubicado en el cantón Latacunga - Oña Ramirez, Jonathan Manuel (2022)
The present thesis project consists of developing and implementing a sale and billing system, one the main characteristics this system is the ease billing, further, the different existing products sales, thus solving the specific needs, helping to improve the employee’s work performance from ”Don Cando" supermarket, where the processes for said management are performed a traditional way, written documents causing a time and information great loss, for this reason, the aim is focused about a web application technological proposal, what systematizes the products sales and billing process for the development, it was used free software tools, such as: PHP, Laravel, MySQL and the Visual Studio text editor Code, It was also used a research methodology, which goes according to the research type: Bibliographic, Technological and Field, by using data collection techniques and instruments, such as: observation, interview and survey, in order to identify the main needs from supermarket. Within the application process was used the XP methodology, which allowed monitoring throughout the project course.